Fasciolasis in children of three districts of Junin, Perú - Mantari T., Carina (2012)
The objective of this study was to determine the prevalence of fasciolasis caused by Fasciola hepatica in children of three districts of Junin, Peru and its association with age, gender and location. It was collected 312 faecal samples from children aged 4 to 12 years in the Masma (n=128) and Llocllapampa (n=70) districts, province of Jauja, and Santa Rosa de Ocopa district (n=114), province of Concepcion, in August and September, 2009. Samples were analyzed by the fast sedimentation coprologic technique. The results showed a prevalence of 11.7% in Masma and 0.9% in Santa Rosa de Ocopa (p<0.05), whereas all samples from Llocllapampa district were negative. There was not statistical association between gender and age with presence of infection. These findings confirm the persistence of the infection in some areas of Junin.